2013
DOI: 10.1038/nrd4126
|View full text |Cite
|
Sign up to set email alerts
|

New avenues for anti-epileptic drug discovery and development

Abstract: Despite the introduction of over 15 third-generation anti-epileptic drugs, current medications fail to control seizures in 20-30% of patients. However, our understanding of the mechanisms mediating the development of epilepsy and the causes of drug resistance has grown substantially over the past decade, providing opportunities for the discovery and development of more efficacious anti-epileptic and anti-epileptogenic drugs. In this Review we discuss how previous preclinical models and clinical trial designs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
486
1
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 552 publications
(515 citation statements)
references
References 155 publications
7
486
1
21
Order By: Relevance
“…Previous publications have addressed the predictability of key models used in therapy development, their appropriateness for certain types of seizures or epilepsies, and suggested changes in the way these are used in therapy development 5, 6, 7, 8, 9, 10, 11, 50, 51, 52, 53…”
Section: Opportunities To Narrow the Preclinical‐clinical Trial Gap Amentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications have addressed the predictability of key models used in therapy development, their appropriateness for certain types of seizures or epilepsies, and suggested changes in the way these are used in therapy development 5, 6, 7, 8, 9, 10, 11, 50, 51, 52, 53…”
Section: Opportunities To Narrow the Preclinical‐clinical Trial Gap Amentioning
confidence: 99%
“…Rigor and transparency issues have been covered extensively in other previous publications 5, 6, 7, 8, 9, 10, 11, 50, 51, 52, 53. Assuming that appropriate rigor has been applied in the studies, preclinical findings may not be confirmed in clinical trials either because they have no true clinical relevance or because clinical trials do not test the appropriate scenarios.…”
Section: Opportunities To Narrow the Preclinical‐clinical Trial Gap Amentioning
confidence: 99%
“…Animal models have, since 1937, been the foundation on which many new therapies have been identified for the treatment of symptomatic epilepsy [1][2][3]. The successful identification of several new antiepileptic (or anti-seizure) drugs (AEDs) since the 1990s clearly supports the value of animal models in the early identification of promising new drugs for the patient with epilepsy [1].…”
Section: Introductionmentioning
confidence: 99%
“…These manipulations result largely in “me‐too” drugs with similar efficacy rather than in a fundamental change to much‐needed, substantially more effective or better‐tolerated drugs compared with current medications 4, 5. A much more promising method, currently gaining momentum, is to design drugs to modify a molecular target presumed to be involved in seizure generation 4, 5. Such target‐based strategies offer the potential for more fundamental advance than simply manipulating the structure of existing drugs.…”
Section: Today's Theories and Practices Which May Not Withstand The Tmentioning
confidence: 99%
“…Also, other aspects affect response but cannot have any relationship to drug target or transporters, for instance: etiology of the epilepsy, epilepsy syndrome, extent or position of a brain lesion, environmental factors such as nutrition, lack of sleep, hepatic enzyme induction, drug receptor regulation, drug dose, pharmacokinetics, and comedication. In fact, none of the commonly proposed theories is able to convincingly explain drug resistance in focal epilepsy 4, 5…”
Section: Today's Theories and Practices Which May Not Withstand The Tmentioning
confidence: 99%